2016
DOI: 10.1002/biof.1325
|View full text |Cite
|
Sign up to set email alerts
|

miR‐346 and miR‐582‐3p‐regulated EG‐VEGF expression and trophoblast invasion via matrix metalloproteinases 2 and 9

Abstract: Endocrine gland-derived vascular endothelial growth factor (EG-VEGF) is an important regulator for embryo implantation and placental development, and is clinically associated with several obstetric disorders related to insufficient or inappropriate trophoblast invasion, such as recurrent abortion, preeclampsia, and intrauterine fetal growth restriction. This study was performed to identify the microRNAs targeting EG-VEGF, and evaluate the regulatory effect on trophoblast biology. miR-346 and miR-582-3p were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 49 publications
0
45
0
1
Order By: Relevance
“…Furthermore, Su et al (30) reported that miR-346 regulated endocrine gland-vascular endothelial growth factor (EG-VEGF)-induced trophoblast invasion by inhibiting MMP-2 and MMP-9, although it had only a limited effect on TIMP-1 and TIMP-2. consistently in the present study, it was found that the effect of downregulated miR-346 on invasion-associated enzymes was similar to that of upregulated LRP6, which was found to promote the expression of MMP-2 and MMP-9 and to inhibit the expression of TIMP-1 and TIMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Su et al (30) reported that miR-346 regulated endocrine gland-vascular endothelial growth factor (EG-VEGF)-induced trophoblast invasion by inhibiting MMP-2 and MMP-9, although it had only a limited effect on TIMP-1 and TIMP-2. consistently in the present study, it was found that the effect of downregulated miR-346 on invasion-associated enzymes was similar to that of upregulated LRP6, which was found to promote the expression of MMP-2 and MMP-9 and to inhibit the expression of TIMP-1 and TIMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 11 miRNAs downregulated in EVs from high oxygen tension on Day 3, miR-15a, miR-125a, miR-195, miR-125b, and miR-346 were previously investigated in embryonic or placental cells. The miRNA-346 has been described as a regulator of trophoblast invasion and migration in humans, while miR-195 is associated with an important paracrine effect on angiogenesis (Almeida et al, 2015;Su, Tsai, Tsai, Chen, & Kuo, 2016). The miR-125 family members, miR-125a and miR-125b play a role in cellular differentiation in mouse embryonic stem cells (K. Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Using HTR8/SVneo, JEG-3 or BeWo trophoblast cell lines, several studies have suggested that miRNAs also regulate EVT motility by targeting other genes involved in regulating cell invasion. Both miR-346 and miR-582-3p targeted endocrine-gland-derived vascular endothelial growth factor (EG-VEGF) as well as matrix metalloproteinase 2 (MMP2) and MMP9, and strongly inhibited the migratory and invasive abilities of trophoblasts (Su et al 2017). Similarly, miR-93 (Pan et al 2017) and miR-204 (Yu et al 2015), which targeted MMP2 and MMP9, respectively, inhibit cell invasion.…”
Section: Mirnas In Trophoblast Differentiation Migration and Invasionmentioning
confidence: 99%